More Than Just Milk Lactation Science Symposium - Geddes, Donna; Stinson, Lisa; Perrella, Sharon; Gridneva, Zoya; McEachran, Jacki (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This book focuses on advanced research topics on human lactation, such as breastfeeding experiences, milk composition and production, COVID-19 and human milk, food allergens in human milk, the human milk microbiome, and the impacts of human milk on infant growth and development. The symposium proceedings aim to add diversity, passion, and innovation to lactation research and have a positive impact on mothers, infants, and communities worldwide, showcasing integrative mother/infant-centered research.